Expression and Clinical Relevance of SOX9 in Gastric Cancer. (2nd June 2019) - Mesquita, Patrícia; Freire, Ana F.; Lopes, Nair; Gomes, Rosa; Azevedo, Daniela; Barros, Rita; Pereira, Bruno; Cavadas, Bruno; Pópulo, Helena; Boaventura, Paula; David, Leonor; Pereira, Luísa; et al.
Abstract : Gastric cancer is one of the most frequent tumours and the third leading cause of cancer-related death worldwide. The investigation of new biomarkers that can predict patient outcome more accurately and allow better treatment and follow-up decisions is of crucial importance. SOX9 (sex-determining region Y (SRY)-box 9) is a regulator of cell fate decisions in embryogenesis and adulthood. Here, we sought to ascertain the relevance of SOX9 transcription factor as a prognostic marker in gastric cancer. SOX9 expression was analyzed by immunohistochemistry in 333 gastric adenocarcinoma cases, and its association with clinicopathological and follow-up data was evaluated. SOX9 nuclear expression was absent in 17% of gastric cancer cases and predicted worse disease-free survival (P = 0.03 ). SOX9 expression was associated with lower risk of relapse in Cox univariable analysis (HR = 0.58 ; 95%CI = 0.35 -0.97;P = 0.04 ). The prognostic value of SOX9 was more pronounced in tumours with expansive growth (P = 0.01 ) or with venous invasion (P = 0.02 ). Two validation cohorts from the Cancer Genome Atlas (TCGA) and the Asian Cancer Research Group (ACRG) confirmed that low SOX9 expression was significantly associated with poor patient outcome. In conclusion, we have identified SOX9 as a biomarker of disease relapse in gastric cancer patients. Further experiments are needed to elucidate its biological relevance at the cellular level.